2022
DOI: 10.3389/fonc.2022.969452
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided posterior quadratus lumborum block can reduce postoperative opioid consumption and promote rapid recovery in patients undergoing sutureless laparoscopic partial nephrectomy: A triple-blind, randomized, controlled study

Abstract: PurposeWe hypothesized that posterior quadratus lumborum block would reduce postoperative opioid consumption and improve the quality of recovery in patients undergoing sutureless laparoscopic partial nephrectomy.Materials and methodsThe study included 60 patients, ages 18−65 with American Society of Anesthesiologists scores of I-II scheduled for elective sutureless laparoscopic partial nephrectomy. Before general anesthesia, 60 participating patients were randomly allocated to receive a 30-ml injection posteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Li et al [19] used QLB-I and QLB-II after LN, both using 0.4% ropivacaine 30ml, the study results showed that the two blocks did not reduce opioid consumption, but improved analgesia within 24 hours after surgery. Zhu et al [20] performed QLB-II before LN and injected 30ml of 0.375% ropivacaine after reaching the block site. The study showed that the cumulative consumption of sufentanil within 12 hours after surgery was lower in the intervention group, and the quality of recovery was higher at 48 hours after surgery.…”
Section: Disscussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al [19] used QLB-I and QLB-II after LN, both using 0.4% ropivacaine 30ml, the study results showed that the two blocks did not reduce opioid consumption, but improved analgesia within 24 hours after surgery. Zhu et al [20] performed QLB-II before LN and injected 30ml of 0.375% ropivacaine after reaching the block site. The study showed that the cumulative consumption of sufentanil within 12 hours after surgery was lower in the intervention group, and the quality of recovery was higher at 48 hours after surgery.…”
Section: Disscussionmentioning
confidence: 99%
“…Zhu et al [20] performed QLB-II before LN and injected 30ml of 0.375% ropivacaine after reaching the block site. The study showed that the cumulative consumption of sufentanil within 12 hours after surgery was lower in the intervention group, and the quality of recovery was higher at 48 hours after surgery.…”
Section: Disscussionmentioning
confidence: 99%
“…function and the mobilization time after surgery were significantly earlier in SQLB group than the control group for laparoscopic nephrectomy in a randomized controlled trial. Similarly, in a triple-blind, randomized, controlled study for laparoscopic partial nephrectomy, by Zhu et al 44 showed the time to the patient's first excretion, ambulation, and drainage tube removal were shorter in the QLB group compared with the control group. Likewise, other studies have reported that compared with GA, QLB for patients undergoing abdominal surgery shortened the first time of getting up, flatus and taking semi-liquid diet, findings consistent with our study.…”
mentioning
confidence: 91%